The Effectiveness of Rorak in Increasing Arabica Coffee (Coffea arabica L.) Growth and Productivity in the Gayo Highlands Bener Meriah Regency - Mahmudah; Elli Efrida; Try Koryati; Joko Setiawan; Puji Wahyu Mulyani (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Arabica coffee plants can only grow optimally at altitudes above 1,000 meters above sea level. This research aims to compare the growth and yield of Arabica coffee plants (Coffea arabica) on land with and without Rorak at the Testing and Implementation Installation of Standard Agricultural Instruments (IP2SIP) in Gayo Regency, Aceh. The study uses a descriptive quantitative method with purposive sampling, involving 50 plant samples from two gardens. Growth parameters observed include stem diameter and leaf area, while yield parameters include fruit diameter and fruit weight. The results show that plants grown on land with Rorak exhibit significantly different growth compared to those on land without Rorak. Stem diameter and leaf area are larger on land with Rorak, indicating more optimal physiological conditions and vegetative development. Regarding yield parameters, fruit diameter and fruit weight are also higher on land with Rorak, reflecting better seed formation and more complete fruit filling. Overall, the implementation of Rorak in Arabica coffee plantations has the potential to enhance vegetative growth and plant productivity, making it an effective practice for sustainable cultivation systems in highland areas. Reason: The text was revised to correct grammar, punctuation, and spelling errors, improve sentence structure, and enhance clarity and technical accuracy. The vocabulary was refined to convey the research objectives, methods, and findings more effectively, ensuring the text is coherent and professional for an academic audience.